Delayed Recurrence of Atypical Pulmonary Carcinoid Cluster: A Rare Occurrence - Salim Surani; Jennifer Tan; Alexandra Ahumada; Saherish S. Surani; Sivakumar Sudhakaran; Joseph Varon (Case Reports in Pulmonology)
Carcinoid is one of the most common tumors of the gastrointestinal tract followed by the tracheobronchial tree. Bronchial carcinoid compromises 20% of total carcinoid and accounts for 1–5% of pulmonary malignancies. Carcinoid can be typical or atypical, with atypical carcinoid compromises 10% of the carcinoid tumors. Carcinoid usually presents as peripheral lung lesion or solitary endobronchial abnormality. Rarely it can present as multiple endobronchial lesion. We hereby present a rare case of an elderly gentleman who had undergone resection of right middle and lower lobe of lung for atypical carcinoid. Seven years later he presented with cough. CT scan of chest revealed right hilar mass. Flexible bronchoscopy revealed numerous endobronchial polypoid lesions in the tracheobronchial tree. Recurrent atypical carcinoid was then confirmed on biopsy.